Inovasi Aplikasi Sistem Informasi Rekapitulasi (Sirekap) dalam Peningkatan Pelayanan Komisi Pemilihan Umum (KPU) Kota Surabaya - Muchammad Nur Salim; Eva Hany Fanida; Meirinawati M; Deby Febriyan Eprilianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Recapitulation Information System (Sirekap) is an e-government-based innovation designed to support transparency, accountability, effectiveness, and efficiency in the vote recapitulation stage of elections. This study employed a descriptive qualitative research method. Data were collected through interviews, observations, literature review, and documentation. The findings indicate that the implementation of SIREKAP at the General Election Commission (KPU) of Surabaya City has fulfilled most of the public sector innovation success indicators proposed by Bugge et al. (2018). The innovation has improved public service quality by accelerating the dissemination of election result information, enhancing transparency, and increasing the efficiency of the vote recapitulation process. Nevertheless, further improvements in human resource capacity, information technology infrastructure, and system evaluation are necessary to ensure that the implementation of SIREKAP becomes more effective and sustainable.